Epidemiological Profile of Meningitis following Pentavalent Vaccination in Iran: Impact of Vaccine Introduction - Saber Heidari; Manoochehr Karami; Seyed Mohsen Zahraei; Iraj Sedighi; Fatemeh Azimian Zavareh (Springer, 2021)
Ensuring the effectiveness of the Haemophilus influenza type b (DTwP-Hib-HepB) vaccine in reducing meningitis is an essential approach in evaluating the effectiveness of the vaccine. The study aimed to address the epidemiology of meningitis following pentavalent vaccination in Iran. Data on meningitis patients from 21st March 2011 to 21st July 2018 were extracted from the National Notifiable Diseases Surveillance System. This information was divided into two equal periods before the pentavalent vaccine introduction (21st March 2011 to 17th November 2014) and after the introduction (18th November 2014 to 21st July 2018). The number of patients in the study period was 53,174 cases. More than 55% of patients were under 5 years old. Males (63.34%) were more than females (36.06%). The death rate was reduced to 2.1%; also, the proportion of confirmed cases caused by H. influenzae type b was 6.7% before the pentavalent vaccine introduction. The corresponding value following vaccine introduction equals to 3.6%. The proportion of children under five has decreased from 4.4% to 1.9%. This value indicates a 46.2% decrease in the meningitis of all ages and a 57% decrease in children under five dues to H. influenzae vaccination. The results of the study indicate the effectiveness of the vaccine due to changes in meningitis caused by H. influenzae type b after vaccination compared with no vaccination. Therefore, it is advisable to continue the full immunization coverage with the pentavalent vaccine.